2015
DOI: 10.1186/s13104-015-1354-y
|View full text |Cite
|
Sign up to set email alerts
|

Simple viral/minimal piggyBac hybrid vectors for stable production of self-inactivating gamma-retroviruses

Abstract: Background Transient production of gamma-retroviruses, including self-inactivating (SIN) retroviruses, is a common method for rapidly generating virus capable of gene delivery. Stable (continuous) production of virus is preferable to transient production for clinical and biotechnology purposes, however, because it allows for significant quantities of a uniform virus to be generated over a prolonged period of time, thus allowing for longitudinal functional studies and quality analysis. Unfortunately, stable pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…In previous studies, we detailed its construction and demonstrated its ability to transpose cells as efficiently as full-length piggyBac transposons 11 ; we also demonstrated that this vector can be used for the rapid generation and purification of packaging cells capable of stably producing self-inactivated gamma-retroviruses. 26 Here, we show that this vector can be used to successfully integrate a 15 kb transgenic sequence into target cells, twice the capacity of retroviral vectors which are currently the most popular method for stable gene delivery. 27 While the integration efficiency of the minimal piggyBac system decreased as the size of the delivered insert increased, the largest transposon was still successfully integrated in 5% of transfected HEK293 cells making these vectors an attractive option for gene delivery.…”
Section: Discussionmentioning
confidence: 89%
“…In previous studies, we detailed its construction and demonstrated its ability to transpose cells as efficiently as full-length piggyBac transposons 11 ; we also demonstrated that this vector can be used for the rapid generation and purification of packaging cells capable of stably producing self-inactivated gamma-retroviruses. 26 Here, we show that this vector can be used to successfully integrate a 15 kb transgenic sequence into target cells, twice the capacity of retroviral vectors which are currently the most popular method for stable gene delivery. 27 While the integration efficiency of the minimal piggyBac system decreased as the size of the delivered insert increased, the largest transposon was still successfully integrated in 5% of transfected HEK293 cells making these vectors an attractive option for gene delivery.…”
Section: Discussionmentioning
confidence: 89%
“…An example is the advent of self-inactivating vectors that reduce the oncogenic risks associated with retroviruses and lentiviruses. Similarly, third-generation adenoviral vectors are designed to minimize unwanted immune activation ( Troyanovsky et al, 2015 ; Shaw and Suzuki, 2019 ).…”
Section: Advantages and Limitations Of Gene Therapy In The Context Of...mentioning
confidence: 99%